If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4b + -3)(5b + 6) = 0 Reorder the terms: (-3 + 4b)(5b + 6) = 0 Reorder the terms: (-3 + 4b)(6 + 5b) = 0 Multiply (-3 + 4b) * (6 + 5b) (-3(6 + 5b) + 4b * (6 + 5b)) = 0 ((6 * -3 + 5b * -3) + 4b * (6 + 5b)) = 0 ((-18 + -15b) + 4b * (6 + 5b)) = 0 (-18 + -15b + (6 * 4b + 5b * 4b)) = 0 (-18 + -15b + (24b + 20b2)) = 0 Combine like terms: -15b + 24b = 9b (-18 + 9b + 20b2) = 0 Solving -18 + 9b + 20b2 = 0 Solving for variable 'b'. Factor a trinomial. (-6 + -5b)(3 + -4b) = 0Subproblem 1
Set the factor '(-6 + -5b)' equal to zero and attempt to solve: Simplifying -6 + -5b = 0 Solving -6 + -5b = 0 Move all terms containing b to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -5b = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -5b = 0 + 6 -5b = 0 + 6 Combine like terms: 0 + 6 = 6 -5b = 6 Divide each side by '-5'. b = -1.2 Simplifying b = -1.2Subproblem 2
Set the factor '(3 + -4b)' equal to zero and attempt to solve: Simplifying 3 + -4b = 0 Solving 3 + -4b = 0 Move all terms containing b to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4b = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4b = 0 + -3 -4b = 0 + -3 Combine like terms: 0 + -3 = -3 -4b = -3 Divide each side by '-4'. b = 0.75 Simplifying b = 0.75Solution
b = {-1.2, 0.75}
| 51-9-6=v | | k+10=-3 | | HX=WQx | | P=5L-4W | | (4-i)-(7+2i)= | | x^4-16x^3=y^3 | | 4m-12=91+5m | | y-(-1)=-5 | | -4n+5=1-3n | | h=-16t^2+88t | | 3/4x-2=1 | | 6x+158=8x+188 | | 19=2x+11 | | -22d-3d=2d+d-3d | | 9/8X3/5 | | 1/2x13=9 | | 1+2n+3n=9+4n | | 6x+7=4x+2x | | 2w-4=8 | | 6-10n=36 | | -6i*6i= | | 6C-7=0 | | 2x(4x-5)=20 | | 72=180-2z | | .75x+.5y=1.25 | | 1=6+96x-16x^2 | | m-10=3.3 | | .75y+.5x=1.25 | | 2(x-8)-3x(x+2)=-24 | | 5(3/4x−1)=2x | | 1/2(20-4x)=5x-2 | | .5x+.75y=1.25 |